2000
DOI: 10.1017/s0033291799002263
|View full text |Cite
|
Sign up to set email alerts
|

Decentring and distraction reduce overgeneral autobiographical memory in depression

Abstract: Background. Increased recall of categorical autobiographical memories is a phenomenon unique to depression and post-traumatic stress disorder, and is associated with a poor prognosis for depression. Although the elevated recall of categorical memories does not change on remission from depression, recent findings suggest that overgeneral memory may be reduced by cognitive interventions and maintained by rumination. This study tested whether cognitive manipulations could influence the recall of categorical memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
157
1
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(182 citation statements)
references
References 32 publications
19
157
1
5
Order By: Relevance
“…Williams, 1996). Second, present findings are consistent with the suggestion (Watkins and Teasdale, 2001) that it is specifically ruminative, analytical, thinking that maintains overgeneral memory; interventions that have previously been shown to reduce overgeneral memory in depression in the short term (Watkins and Teasdale, 2001;Watkins et al, 2000) have, like the experiential induction in the present study, induced a non-analytical mode of processing. Third, the present study demonstrated a dissociation between the effects of the experiential and analytical inductions on overgeneral memory and their effects on mood, the inductions producing significantly different effects on the former, but very similar effects on the latter.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Williams, 1996). Second, present findings are consistent with the suggestion (Watkins and Teasdale, 2001) that it is specifically ruminative, analytical, thinking that maintains overgeneral memory; interventions that have previously been shown to reduce overgeneral memory in depression in the short term (Watkins and Teasdale, 2001;Watkins et al, 2000) have, like the experiential induction in the present study, induced a non-analytical mode of processing. Third, the present study demonstrated a dissociation between the effects of the experiential and analytical inductions on overgeneral memory and their effects on mood, the inductions producing significantly different effects on the former, but very similar effects on the latter.…”
Section: Discussionsupporting
confidence: 90%
“…First, this study provides further evidence that overgeneral memory in depression is modifiable over short time periods, replicating and extending previous findings (Watkins and Teasdale, 2001;Watkins et al, 2000). This evidence suggests that overgeneral memory recall depends upon the continuing dynamic activation of a particular state or mode of processing at the time of recall, rather than reflecting a more static trait-like feature of depressionprone individuals, as had been previously suggested (e.g.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The range of measures of ACT processes is still limited, however. A wide range of concepts and measures seem to overlap with the ACT model, and researchers are beginning to explore connections with such concepts as distress tolerance (Brown xxx), learned industriousness (Eisenberger, 1992), thought suppression (Wenzlaff & Wegner, 2000), delay discounting (Myerson & Green, 1995), strivings (Sheldon, Ryan, Deci, & Kasser, 2004), mindfulness (Baer xxx ), metacognition (Wells, 2000), decentering (Watkins, Teasdale, & Williams, 2000) and the like. As the ACT / RFT research program expands a wider variety of theoretically coherent measures, including some outside of self-report, seem likely to be available to refine the tests of an ACT model.…”
Section: Studies Of the Act Model: Correlational Studiesmentioning
confidence: 99%
“…Embora a propensão para recuperar memórias autobiográficas de maneira supergeneralizada seja considerada como uma característica estável dos depressivos (Brittlebank et al, 1993), existem evidências consistentes de que ela é sujeita a modificações, pelo menos em curto prazo (Watkins et al, 2000;Watkins e Teasdale, 2001;Williams et al, 2000). Os indícios empíricos quanto à possibilidade de haver mudanças no padrão de processamento mnemônico supergeneralizado são de suma importância, uma vez que oferecem bases sólidas que justificam o engajamento dos psicoterapeutas em técnicas para trabalhar esse mecanismo cognitivo perpetuador da depressão com seus pacientes.…”
Section: Implicações Para Terapia Cognitivaunclassified